Neuropathology associated with exposure to different concentrations and species of mercury: A review of autopsy cases and the literature - O’Donoghue, John L.; Watson, Gene E.; Brewer, Rubell; Zareba, Grazyna; Eto, Komyo; Takahashi, Hitoshi; Marumoto, Masumi; Love, Tanzy; Harrington, Donald; Myers, Gary J. (Neurotoxicology (Park Forest South), 2020)
•Mean total mercury in the cerebrum of people with no known exposure was 16 ppb.•Mean total mercury in the cerebrum of Seychellois consuming fish was 129−182 ppb.•No pathology was observed in the brains of Seychellois who consumed fish regularly.•Total brain mercury approaches steady state during gestation or shortly thereafter.•Different Hg species are associated with differing neuropathological patterns. Human exposure to mercury (Hg) is widespread and both organic and inorganic Hg are routinely found in the human brain. Millions of people are exposed to methyl Hg (MeHg) due to the consumption of fish and to inorganic Hg from dental amalgams, small scale gold mining operations, use of Hg containing products, or their occupations. Neuropathology information associated with exposures to different species of Hg is primarily based on case reports of single individuals or collections of case studies involving a single species of Hg at toxic exposure levels such as occurred in Japan and Iraq. This study brings together information on the neuropathological findings and deposition of Hg in the central nervous system of people exposed to different species of Hg at varying concentrations. The low dose exposures were lifetime exposures while the high dose exposures were generally acute or short term by different exposure routes with survival lasting various lengths of time. Total and inorganic Hg deposits were identified in formalin-fixed, paraffin embedded tissues from both low and high exposure Hg cases. Low concentration exposures were studied in adult brains from Rochester, New York (n = 4) and the Republic of Seychelles (n = 17). Rochester specimens had mean total Hg concentrations of 16−18 ppb in the calcarine, rolandic, and cerebellar cortices. Inorganic Hg averaged between 5–6 ppb or 30–37% for the cerebral and cerebellar cortices of the Rochester subjects. Total Hg was approximately 10-fold higher in specimens from Seychelles, where consumption of ocean fish is high and consequently results in exposure to MeHg. The predominant Hg species was MeHg in both the Rochester and Seychelles brain specimens. Histologically, cerebral and cerebellar cortices from Rochester and Seychelles specimens were indistinguishable. High concentration exposures were studied in brains from four adults who were autopsied at variable time periods after exposure to organic Hg (methyl or dimethyl) or inorganic Hg (inhaled vapor or intravenous injection of metallic Hg). In contrast to the Seychellois adults, these individuals had acute or subacute exposures to lethal or significantly higher concentrations. The pattern of Hg deposition differed between subjects with high organic Hg exposure and high inorganic Hg exposure. In the organic Hg cases, glia (astrocytes and microglia) and endothelial cells accumulated more Hg than neurons and there were minimal Hg deposits in cerebellar granule and Purkinje cells, anterior horn motor neurons, and neocortical pyramidal neurons. In the inorganic Hg cases, Hg was seen predominantly in neurons, vascular walls, brainstem, and cerebellar and cerebral deep gray nuclei. The presence of inorganic Hg in neural and neural supporting cells in the four high exposure Hg cases was not closely correlated with cellular pathology; particularly in the inorganic Hg cases. Different Hg species are associated with differing neuropathological patterns. No neuropathological abnormalities were present in the brains of either Rochester or Seychelles residents despite substantial differences in dietary MeHg exposure. Increasing concentrations of inorganic Hg were present in the brain of relatively low exposure subjects with increasing age.